Overall Work and Practice Satisfaction of Licensed Clinical Social Workers in the National Health Service Corps Loan Repayment Program. Issue 1 (5th May 2021) - Yun, Jonathan; Zerden, Lisa de Saxe; Cuddeback, Gary; Konrad, Thomas; Pathman, Donald E
: Little is known about the job satisfaction of licensed clinical social workers (LCSWs) participating in the National Health Service Corps (NHSC) federal Loan Repayment Program (LRP). Employee satisfaction in organizations is important for organizational well-being and to decrease turnover. A satisfied NHSC LCSW workforce is also important given the array of services it provides, especially in rural and underserved areas. This study examined the work satisfaction of 386 LCSWs participating in the NHSC LRP in 21 states. Rural upbringing, being older than 40 years, and a higher salary were significantly associated with overall work and practice satisfaction. In addition, satisfaction with administration, staff and the practices' linkages to other health providers, the mission of the practice, and connection with patients were strongly associated with overall work and practice satisfaction. To our knowledge, this is the first study to examine the work and practice satisfaction of LCSWs participating in the NHSC LRP, and our findings have the potential to inform the NHSC's strategies in managing and retaining LCSWs.